Genetic and Molecular Evaluation of SQSTM1/p62 on the Neuropathologies of Alzheimer’s Disease - Dong, Wei; Cui, Meng-Chao; Hu, Wen-Zheng; Zeng, Qi; Wang, Yi-Long; Zhang, Wei; Huang, Yue (Frontiers in Aging Neuroscience, 2022)
Sequestosome 1 (SQSTM1)/p62 is a multifunctional scaffolding protein and plays a major role in the cellular processes of autophagy, upregulation of which has been shown in several neurodegenerative disorders, including Alzheimer’s disease (AD). To investigate its genetic effects and relationship with AD pathologies, we analyzed the genetic associations of SQSTM1 rs4935 with the risk of AD and the levels of AD biomarkers using the AD Neuroimaging Initiative (ADNI) Database. We further analyzed the distribution pattern of p62 immunoreactivity in relation to AD pathologies in the postmortem human brain tissues from AD and non-AD controls. We found that SQSTM1 rs4935 was not associated with the risk of AD, but its T allele was significantly associated with decreased β-amyloid (1–42) (Aβ42) levels in the cerebral spinal fluid (CSF) of patients with AD (β = −9.336, p = 0.022). In addition, p62 immunoreactivity in AD is increased, but it shows an inverse relationship to Aβ deposition. A small proportion of senile plaques show p62 positive neurites. Our results suggest that SQSTM1/p62 may play an important role in the progression of AD via associations with Aβ42 levels in CSF and Aβ deposition in the brain of patients with AD.